2016
DOI: 10.3748/wjg.v22.i41.9044
|View full text |Cite
|
Sign up to set email alerts
|

Concise review: Interferon-free treatment of hepatitis C virus-associated cirrhosis and liver graft infection

Abstract: Chronic hepatitis C is a major reason for development of cirrhosis and hepatocellular carcinoma and a leading cause for liver transplantation. The development of direct-acting antiviral agents lead to (pegylated) interferon-alfa free antiviral therapy regimens with a remarkable increase in sustained virologic response (SVR) rates and opened therapeutic options for patients with advanced cirrhosis and liver graft recipients. This concise review gives an overview about most current prospective trials and cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 84 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…With the advent of DAAs, IFN-free therapeutic regimens for the treatment of chronic HCV infection are now allowed. These regimens lead to remarkable improvements in sustained virologic response (SVR12), defined as undetectable HCV RNA levels 12 weeks after the end of the treatment, thereby providing therapeutic options to patients with contraindications or low prior SVR to IFN-based regimens 46. In particular, regimens using sofosbuvir (SOF), a pan-genotypic HCV nucleotide polymerase inhibitor, provide more convenient dosing schedules by shortening the duration of treatment to 12–24 weeks and lead to cure rates close to 90% 7–11…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of DAAs, IFN-free therapeutic regimens for the treatment of chronic HCV infection are now allowed. These regimens lead to remarkable improvements in sustained virologic response (SVR12), defined as undetectable HCV RNA levels 12 weeks after the end of the treatment, thereby providing therapeutic options to patients with contraindications or low prior SVR to IFN-based regimens 46. In particular, regimens using sofosbuvir (SOF), a pan-genotypic HCV nucleotide polymerase inhibitor, provide more convenient dosing schedules by shortening the duration of treatment to 12–24 weeks and lead to cure rates close to 90% 7–11…”
Section: Introductionmentioning
confidence: 99%
“…The tolerability of DAA based regimens is definitely better with exception of those who have impaired renal function. 55 Most of the studies shown in Table 1 have shown good results. What is not shown in the table is that there is also an improvement in liver function and reversal of decompensation to some extent as more and more patients become aviremic.…”
Section: Feasibility and Effectivenessmentioning
confidence: 92%
“…Direct-acting antiviral drugs have revolutionized HCV treatment and have led to a sustained viral response and presumed cure at 12 weeks in more than 95% of cases across all HCV genotypes. 20 Given the recent development of effective and well-tolerated treatments, primary care physicians have assumed a pivotal role in screening for HCV.…”
Section: Chronic Hepatitis B Virus and Hepatitis C Virus Infectionsmentioning
confidence: 99%